Моделювання механічних передач - Дереза, Олена Олександрівна; Дереза, Елена Александровна; Dereza, Olena; Дереза, Сергій Володимирович; Дереза, Сергей Владимирович; Dereza, Serhii (ТДАТУ, 2020)
UK: У статті проаналізовано основні програмні продукти комп'ютерного моделювання з використанням 3D-технологій при розрахунках і проектуванні механічних передач. 3D моделювання набагато ефективніше традиційних креслень і двомірних зображень проектованих виробів, оскільки дозволяє в деталях оцінити характеристики об'єкта на початкових етапах роботи. Встановлено, що найбільш точні моделі механічних передач можна отримати в більш популярних додатках для КОМПАС-3D - SolidWorks. У цих програмах є один незаперечний плюс, навіть у порівнянні з більш потужними 3D додатками - все просто і швидко будується і збирається, створені 3D-моделі реалізується автоматично відповідно до набору заданих параметрів. Для аналізу міцності і жорсткості елементів механічних передач використовуються стрижневі конечноелементні моделі, максимально адаптовані до розрахункових схем даного типу. Для максимально реалістичного зображення об'ємного графічного об'єкта підходить самий професійний продукт - 3ds-max. Для точного побудови колеса простіше створити модель в КОМПАС-3D або в SolidWorks, зберегти з відповідним розширенням і імпортувати в 3ds-max. RU: В статье проанализированы основные программные продукты компьютерного моделирования с использованием 3D-технологий при расчетах и проектировании механических передач. 3D моделирование намного эффективнее традиционных чертежей и двухмерных изображений проектируемых изделий, поскольку позволяет в деталях оценить характеристики объекта на начальных этапах работы. Установлено, что наиболее точные модели механических передач можно получить в более популярных приложениях для КОМПАС-3D, SolidWorks. В этих программах есть один неоспоримый плюс, даже по сравнению с более мощными 3D приложениями - все просто и быстро строится и собирается, созданные 3Dмодели реализуется автоматически соответствии с набором заданных параметров. Для анализа прочности и жесткости элементов механических передач используются стержневые конечноэлементные модели, максимально адаптированные к расчетным схемам данного типа. Для максимально реалистичного изображения объемного графического объекта подходит самый профессиональный продукт - 3ds-max. Для точного построения колеса проще создать модель в КОМПАС-3D или в SolidWorks, сохранить с соответствующим расширением и импортировать в 3ds-max. EN: Computer modeling has become a necessary part of training specialists in various specialties. An engineer who does not have the knowledge and skills of computer simulation programs cannot be considered a full-fledged specialist. The successes achieved in recent years in the field of the use of computer engineering, mathematical modeling and optimization methods, opens up new opportunities for the implementation of highly efficient automation of design works and accelerate on this basis scientific and technological progress in various fields of science and technology. Gears are one of the most common parts of various machines and mechanisms. They are integral components of gears, and the quality and reliability of the devices manufactured depend on how well they will be developed. The basic computer simulation software using 3D technologies in the calculation and design of mechanical gears is analyzed. 3D modeling is much more effective than traditional drawings and two-dimensional images of designed products, because it allows you to evaluate in detail the characteristics of the object in the initial stages of operation. It has been found that the most accurate mechanical gear models are available in the more popular applications for COMPASS-3D, SolidWorks. In these programs there is one clear plus, even compared to more powerful 3D applications - everything is simple and quickly built and assembled, creation of a 3D model is realized automatically according to a set of set parameters. For the analysis of the strength and rigidity of the elements of mechanical transmissions rod finite element models are used, which are maximally adapted to the calculation schemes of this type. For the most realistic image of a 3D graphic object is the most professional product - 3ds-max. For accurate wheel construction, it's easier to build a model in COMPASS-3D or SolidWorks, save with the appropriate extension, and import into 3ds-max.
Моделирование механических передач
Mechanical transmission modeling
Keywords: механічні передачі; евольвентний профіль; 3D-моделювання; КОМПАС; SolidWorks; 3D-технології; 3ds-max; графічний об'єкт; твердотельное моделювання; рендеринг; механические передачи; эвольвентный профиль; 3D-моделирование; 3D-технологии; графический объект; твердотельное моделирование; mechanical gears; involutes profile; 3D modeling; КОМПАС-3D; 3D technologies; graphic object; solid state modeling; rendering